Performance on the Rey-Osterrieth complex figure test and the correlation with the magnetic resonance imaging brain lesion volume in multi-infarct versus small vessel disease dementia - Semnić, Marija D; Semnić, Robert; Nikolašević, Željka; Bugarski Ignjatović, Vojislava V; Vujanić Stankov, Tijana Ž; Kostić, Smiljana; Ocić, Gordana; Kozić, Duško (Vojnosanitetski pregled, 2021)
Background/Aim. Regarding several cognitive domains, including visuospatial and visuoconstructional abilities, little is known about the differences between vascular dementia (VaD) subtypes, even in the most common subtypes, such as multi-infarct dementia (MID) and subcortical ischemic small vessel disease dementia (SSVD). This paper aimed to identify the differences between the performances on the Rey-Osterrieth Complex Figure (ROCF) test in MID and SSVD and correlate the ROCF scores in both groups with magnetic resonance imaging (MRI) ischemic lesion load. Methods. Sixty VaD patients with matching severity of dementia, age, and education were included in this study: 32 with SSVD and 28 with MID according to the NINDS-AIREN (National Institute of Neurological Disorders and Stroke and Association Internationale pour la Recherché et l'Enseignement en Neurosciences) neuroradiological criteria. A quantitative scoring system was performed. ROCF was given to all subjects in three test conditions: copy, immediate recall after 3 minutes, and delayed recall after 45 min. Magnetic resonance imaging (MRI) of the ischemic brain volumes of anterior and posterior lesions, left and right hemispheric lesions, left and right-sided basal ganglia lesions, and total lesion load (TLL) were calculated in both groups. Results. The MID group was more impaired than SSVD on ROCF copy (p = 0.008), immediate recall (p= 0.005) and delayed recall (p = 0.001). There were significant correlations between ROCF copy score and the TLL (p
Keywords: dementia, vascular; cerebrovascular disorders; neurologic manifestations; neurologic examination; magnetic resonance imaging; memory disorders